Modeling of Lightning Events using WRF-derived Microphysical Parameters - Islam, Md Ashraful; Meandad, Javed; Shuvo, Saurav Dey; Kabir, Alamgir (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Numerical simulation of lightning events in Bangladesh has been carried out by using Weather Research and Forecasting Model with Advanced Research Dynamic solver (WRF-ARW). Three major lightning events have been considered for the case study; Case_1, lightning occurrence in Netrokona district in March 24 2017, Case_2, lightning event in Barishal district in April 23 2017, and case_3, lightning event in Sherpur district in April 29, 2018. The model simulation was run in 9 km and 3 km of horizontal resolution using six hourly NCEP-FNL datasets. Yonsei University (YSU) PBL scheme, Rapid Radiative Transfer Model (RRTM) long-wave scheme for radiation, and Kain-Fritsch cumulus parameterization scheme is used for this study. The obtained results from the simulation could reasonably capture the lightning condition of the atmosphere for all the three cases. The WRF simulation give reasonable agreement with the available observational data with some spatial and temporal variations, for example the Convective Available Potential Energy (CAPE) values observed are 1299 J/Kg, 3150 J/kg, 1221 J/kg and CAPE values simulated are 1618 J/kg, 3275 J/kg and 1023 J/kg for case_1, case_2 and case_3 respectively. The regression analysis of the flash count with the microphysical parameters is also studied. It is found that there is strong correlation between the lightning flash counts with the microphysical parameters. This study will help to understand the lightning better and will help to design a better lightning forecasting system. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(2), 2019, P 41-50